The development of competencies required for school principals in Quebec: Adequacy between competency standard and practice - Monique Lambert; Yamina Bouchamma (Arizona State University, 2019)
School principals deal with a variety of increasingly complex responsibilities (Trudeau, 2013). They must therefore develop and hone professional competencies that will enable them to effectively perform their pedagogical, organizational, relational, or administrative duties (Barber, Whelan Clark., 2010; Bisaillon et al., 2009; Darling-Hammond, Meyerson, LaPointe, Orr, 2010; Pont, Nusche, Moorman, 2008). In light of the many societal changes and resulting pressure on schools, many countries have developed competency standards for school principals to redefine the competencies required to successfully fulfill this role (UNESCO, 2006). Quebec has followed suit in this movement with the publication of its first competency standard for school principals in 2008. This document is used during the initial training for future school principals to develop competencies useful for this function. What competencies are needed by school leaders in relation to the challenges they face in their work? What are these challenges? Interviews with school principals (N = 13) allowed us to highlight challenges that arise in their day-to-day activities which allowed us to identify the professional and cross-curricular (behavioural) competencies that they implement to do their job.